Primary Mpox and Secondary Syphilis in an HIV Patient: A Community Hospital Experience - Geocel-Grace Castanares DO; Carlos D'Assumpcao MD; Michelle Fang PharmD; Rick McPheeters DO; Arash Heidari MD (SAGE Publishing, 2023)
Mpox was an emerging outbreak in California in 2022, primarily in major metropolitan areas, as part of the global mpox outbreak declared by World Health Organization in July 2022. Community hospitals outside of major metropolitan areas have seen fewer cases to date, so they may be less equipped to diagnose and treat patients with mpox. They may have limited public health resources commensurate with the area's population density. Mpox may also be superimposed on ongoing local outbreaks of other sexually transmitted infections. We present a case of a person with HIV who contracted mpox and also developed secondary syphilis. Early detection can be beneficial for prompt treatment, decreased burden of disease for the individual, and prevention of further spread of the infection.